KEBIJAKAN PENDIDIKAN GRATIS DI TINGKAT REGIONAL: Konsep dan Pelaksanaan di Kabupaten Rembang - MUHAMMAD ARIF DAHLAN, MUHAMMAD ARIH DAHLAN (Program Magister Ilmu Politik, Universitas Diponegoro, 2011)
AbstractThe substance of the implementation of social welfare is to ensure citizens to meet their basicneeds. The decent Education is one of the basic needs of citizens. However, The policies relating tothe fulfillment of a decent education has been distorted. Such as the phenomenon of free educationpolicy in Indonesia, which is just often becomes a mantra on sale for the politicians during thecampaigns. But ironically, the concept of free education often does not have a clear meaning in theempirical level, whether in relation to the scope, management and the destination. The researcher willtake a case study of free education policy in Rembang District of Central Java. The researcher willexamine the case by implementing public policy approaches. The researcher will explore variousaspects of the program that occur in the stages of pre-formulation, formulation, implementation,evaluation, and feedback of the free education policy.Keywords: social welfare, free education, public policy